Child protection in England: an emerging inequalities perspective. Issue 2 (18th September 2017) - Bywaters, Paul; Sparks, Tim
Abstract : Purpose: In the past 40 years, both health policy and educational policy in England have adopted commitments to reducing socially created inequalities. However, an inequalities perspective has only begun to emerge in relation to child protection, and child welfare services more widely. The purpose of this paper is to chart evidence of these green shoots of a new policy direction which focusses on two aspects: equalising service provision and outcomes for looked after children. Design/methodology/approach: The paper provides an analysis of trends in policies as expressed in official documents, research studies and policy statements. Findings: The paper outlines the argument for a more comprehensive approach to addressing inequalities in child protection and child welfare services, and concludes by suggesting some implications for policy and practice. Originality/value: The paper develops the concept of an inequalities perspective in child protection and outlines key implications.